2020
DOI: 10.1080/87559129.2020.1810700
|View full text |Cite
|
Sign up to set email alerts
|

Grape Polyphenols to Arrest in Vitro Proliferation of Human Leukemia Cells: A Systematic Review and Meta-analysis

Abstract: Leukemia is a heterogeneous group of hemopoietic cancers, which accounts for 2.6% of new cases per year of total cancer incidence worldwide. Grapes and grapederived products, such as grape juice, are naturally rich in polyphenols, bioactive compounds with antioxidant properties. Certain polyphenols have been proved to alter oxidative balance, both in inducing apoptosis in cancer cells and in preventing cancer development via controlling oxidative stress. To assess the therapeutic potential of grape polyphenols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…In the last ten years, numerous review papers and chapters have been published that provide overviews of the chemistry and biochemistry of polyphenols [11,[19][20][21][22], their composition and content in grapes [23], their impacts on human health [24,25], and their interactions with different aspects of human health in more detail, such as anticancer [26], neuroprotective [26][27][28][29][30][31], anti-inflammatory [32][33][34], cardiovascular [35], and anti-diabetic [36] actions. This review aims to combine the most relevant data representing the composition and content of polyphenols in different varieties and organs of grapes, to present the most important techniques of qualitative and quantitative analysis of these compounds, and to give a comprehensive overview of the effects of polyphenols from vines on human health, including antioxidant activity, anti-inflammatory activity, cardiovascular protection, neuroprotective activity, anticancerogenic activity, and antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…In the last ten years, numerous review papers and chapters have been published that provide overviews of the chemistry and biochemistry of polyphenols [11,[19][20][21][22], their composition and content in grapes [23], their impacts on human health [24,25], and their interactions with different aspects of human health in more detail, such as anticancer [26], neuroprotective [26][27][28][29][30][31], anti-inflammatory [32][33][34], cardiovascular [35], and anti-diabetic [36] actions. This review aims to combine the most relevant data representing the composition and content of polyphenols in different varieties and organs of grapes, to present the most important techniques of qualitative and quantitative analysis of these compounds, and to give a comprehensive overview of the effects of polyphenols from vines on human health, including antioxidant activity, anti-inflammatory activity, cardiovascular protection, neuroprotective activity, anticancerogenic activity, and antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…54 In practice, light quality can be used to change the proportion of anthocyanins in callus and to increase the content of a certain molecule among the total anthocyanins, a finding which would be conducive to the upregulation of single compounds. Sixteen kinds of non-anthocyanin phenolic compounds were detected in the red callus of spine grape, belonging to hydroxybenzoic acids (1), hydroxycinnamic acids (1), flavan-3ols (5), and flavonols (9). One hydroxybenzoic acid was detected (PA), and the accumulation of PA was inhibited by red light and darkness.…”
Section: Effect Of Light Quality and Culture Duration On The Proporti...mentioning
confidence: 99%
“…Spine grape contains not only special, volatile, aromatic substances , but is also rich in phenolic acids and flavonoids, including anthocyanins and proanthocyanidins, and phenolic compounds, with strong antioxidant capacity . These natural antioxidants have a number of important human health-promoting activities, like polyphenols from other grape species, including anticardiovascular disease, antidiabetes, antihypertension, anticancer, and antibacterial activities . Good processing characteristics and the ability to promote human health give spine grape a high utilization value and commercial potential.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have shown that consumption of polyphenol-rich foods reduces the risk of oxidative stress-induced disease, due to their antioxidant properties, lowering the accumulation of intracellular reactive oxygen species (ROS) that are important molecules in the development of neurodegenerative, cardiovascular, and cancerous diseases [ 16 , 17 ]. There are in vivo studies and clinical trials using grape polyphenols that have shown their beneficial effects in the treatment of cancer [ 18 , 19 , 20 ] and cardiovascular diseases [ 21 , 22 ]. Moreover, research examining specific polyphenols such as resveratrol has shown them to interfere with numerous metabolic pathways related to the progression of some types of cancer and coronary heart disease [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%